Challenges of Implementing Knowledge Management at the Workplace: A Systematic Literature Review (Dhaka University Journal of Business Studies, 2026)
Despite emerging as a progressive academic discipline, very few studies have so far been conducted on the challenges of implementing knowledge management (KM). Addressing this gap, the present study aims to identify the major challenges organizations typically confront while managing knowledge within the workforce. The study adopts a systematic literature review as a methodical approach to synthesize and evaluate accessible evidence relating to this research aim. A thorough search has been performed across academic databases and relevant journals, resulting in a selection of 54 pertinent research articles and review papers published from 1990 until early 2024, which are then critically reviewed to determine the key challenges. Based on the findings, it can be argued that transparentizing the KM concept; attaining leadership commitment and support; securing adequate managerial assistance; establishing robust technological base; overcoming employee resistance; and assuring effective time management are the major challenges of KM implementation. This review contributes to the literature by exploring the potential complexities involved in KM practices. It might also guide the practitioners in proactively strategizing to meet the challenges in an effective manner.Journal of Business Studies, Vol. XLIV, No. 1, 2025 Page 165-185